2016
DOI: 10.1002/advs.201500312
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance Effect in Inverted Perovskite Solar Cells

Abstract: This work reports on incorporation of spectrally tuned gold/silica (Au/SiO2) core/shell nanospheres and nanorods into the inverted perovskite solar cells (PVSC). The band gap of hybrid lead halide iodide (CH3NH3PbI3) can be gradually increased by replacing iodide with increasing amounts of bromide, which can not only offer an appreciate solar radiation window for the surface plasmon resonance effect utilization, but also potentially result in a large open circuit voltage. The introduction of localized surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 44 publications
0
60
0
Order By: Relevance
“…Because the Au‐NPs are only 2–3 nm in diameter, which is well below the thickness of the conformal coated 20 nm NiO x film, they were able to be fully covered by the NiO x . In this way, direct contact between Au and perovskite could be avoided, thus reducing the possibility of recombination arising from the otherwise formed Au‐perovskite interface and the backflow current via Au‐NPs . The high resolution TEM image exhibited the lattice fringe of Au‐embedded NiO x film (Figure S6c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Because the Au‐NPs are only 2–3 nm in diameter, which is well below the thickness of the conformal coated 20 nm NiO x film, they were able to be fully covered by the NiO x . In this way, direct contact between Au and perovskite could be avoided, thus reducing the possibility of recombination arising from the otherwise formed Au‐perovskite interface and the backflow current via Au‐NPs . The high resolution TEM image exhibited the lattice fringe of Au‐embedded NiO x film (Figure S6c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a recent study reported evidence of electron transfer between perovskite and gold nanoparticle (AuNP)‐based plasmon resonance scattering . As the size and shape of metallic nanostructures play a critical role in achieving panchromatic photon absorption, spherical nanoparticles and nanorods of gold and silver have been previously used in PSCs . Although these plasmonic nanostructures have shown some promise in efficiency enhancement of PSCs, complex nanostructures such as nanostars are of great interest owing to their highly concentrated field intensity around the branched corners and edges to enhance the LHE.…”
Section: Figurementioning
confidence: 99%
“…For comparison, we also fabricated PSCs based on AuNPs‐ and AuNRs‐incorporated TiO 2 photoelectrodes and tested their performances under the same conditions. Some recent studies showed that the incorporation of both AuNPs and AuNRs can significantly improve the PV efficiencies of the PSCs owing to the enhanced LHE and/or reduced the exciton binding energy of the light absorber in the devices . High‐resolution TEM images and UV/Vis of AuNPs, AuNRs, and AuNSs can be found in Figure S2.…”
Section: Figurementioning
confidence: 99%
“…That is to say their light absorption enhancement is mainly ascribed to scattering, and the SPR effect of Au NPs may play an ineffective role. Furthermore, Wang and Snaith have incorporated Au NPs into mesoporous Al 2 O 3 layer, but they proposed that the SPR effect has little influence on light absorption, and ascribed their IPCE enhancement to the improvement of charge separation. Recently, Ye et al incorporated Au NPs into absorber/HTL interface, and they found a more significant enhancements in all photovoltaic parameters mainly due to the improved mobility of the charge carriers .…”
Section: Introductionmentioning
confidence: 99%